Therapeutic Drug Monitoring of Everolimus: A Consensus Report. Issue 2 (April 2016) - Shipkova, Maria; Hesselink, Dennis A.; Holt, David W.; Billaud, Eliane M.; van Gelder, Teun; Kunicki, Paweł K.; Brunet, Mercè; Budde, Klemens; Barten, Markus J.; De Simone, Paolo; Wieland, Eberhard; López, Olga Millán; et al.
Abstract : Abstract: In 2014, the Immunosuppressive Drugs Scientific Committee of the International Association of Therapeutic Drug Monitoring and Clinical Toxicology called a meeting of international experts to provide recommendations to guide therapeutic drug monitoring (TDM) of everolimus (EVR) and its optimal use in clinical practice. EVR is a potent inhibitor of the mammalian target of rapamycin, approved for the prevention of organ transplant rejection and for the treatment of various types of cancer and tuberous sclerosis complex. EVR fulfills the prerequisites for TDM, having a narrow therapeutic range, high interindividual pharmacokinetic variability, and established drug exposure–response relationships. EVR trough concentrations (C0 ) demonstrate a good relationship with overall exposure, providing a simple and reliable index for TDM. Whole-blood samples should be used for measurement of EVR C0, and sampling times should be standardized to occur within 1 hour before the next dose, which should be taken at the same time everyday and preferably without food. In transplantation settings, EVR should be generally targeted to a C0 of 3–8 ng/mL when used in combination with other immunosuppressive drugs (calcineurin inhibitors and glucocorticoids); in calcineurin inhibitor-free regimens, the EVR target C0 range should be 6–10 ng/mL. Further studies are required to determine the clinical utility of TDM in nontransplantation settings. The choice of analytical method and differences between methods should be carefully considered when determining EVR concentrations, and when comparing and interpreting clinical trial outcomes. At present, a fully validated liquid chromatography tandem mass spectrometry assay is the preferred method for determination of EVR C0, with a lower limit of quantification close to 1 ng/mL. Use of certified commercially available whole-blood calibrators to avoid calibration bias and participation in external proficiency-testing programs to allow continuous cross-validation and proof of analytical quality are highly recommended. Development of alternative assays to facilitate on-site measurement of EVR C0 is encouraged. Abstract : Supplemental Digital Content is Available in the Text.